2019
DOI: 10.1371/journal.pone.0226804
|View full text |Cite
|
Sign up to set email alerts
|

What factors do make quality improvement work in primary health care? Experiences of maternal health quality improvement teams in three Puskesmas in Indonesia

Abstract: BackgroundIndonesia has been shifting from ensuring access to health services towards improving service quality. Accreditation has been used as quality assurance (QA) mechanism, first in hospitals and subsequently in primary health care facilities, including Puskesmas (community health centres). QA provides measures of whether services meet quality targets, but quality improvement (QI) is needed to make change and achieve improvements. QI is a cyclical process with cycles of problem identification, solution te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 35 publications
0
43
0
2
Order By: Relevance
“…From the above results, it can be seen that the Tobit model’s fixed effect regression results of population density, degree of opening up, education level, economic development level, urbanization level, technological innovation level and degree of aging are significant. They are driving factors for the public health service capacity of countries in the EU [ 31 ]. However, per capita GDP and the Gini coefficient did not pass the significance test, indicating that there is no direct correlation between per capita GDP and Gini coefficient and public health service capacity.…”
Section: Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the above results, it can be seen that the Tobit model’s fixed effect regression results of population density, degree of opening up, education level, economic development level, urbanization level, technological innovation level and degree of aging are significant. They are driving factors for the public health service capacity of countries in the EU [ 31 ]. However, per capita GDP and the Gini coefficient did not pass the significance test, indicating that there is no direct correlation between per capita GDP and Gini coefficient and public health service capacity.…”
Section: Results Discussionmentioning
confidence: 99%
“…The medical and health resources of economically developed countries are mostly provided to people with a certain economic foundation. Low-income people cannot universally and comprehensively enjoy public health services [ 31 ]. This shows that the gap between the rich and the poor is not related to the capacity of public health services.…”
Section: Results Discussionmentioning
confidence: 99%
“…A study in Ghana also found that managers' capacity to lead is directly influenced by the contextual factors [63]. In Indonesia, a study on factors influencing the success of a PHC quality improvement programme found that strong local leadership and their involvement in resource decision-making were success factors [64].…”
Section: Discussionmentioning
confidence: 99%
“…The policy documents which support the health care framework envision attaining improved health care through stakeholder collaboration [46,51,52]. Stakeholder participation in decision-making and the implementation of health care services was emphasized by respondents as important in collaborative governance at multiple levels of the health system [33,[47][48][49][50][51][52]. While stakeholders played a positive role in primary health care provision, there were no clear mechanisms for controlling or regulating their entry, operations and exit [50].…”
Section: Lack Of Structures For Appropriate Stakeholder Involvementmentioning
confidence: 99%